“An Empire of Beads”? The Making of the Manaus Free Trade Zone - Adrián Lerner Patrón (Iberoamericana. América Latina - España - Portugal)
This article studies the history of Manaus, the largest city in Amazonia and the capital of Amazonas, Brazil’s largest state, between the end of Amazon rubber boom, in the 1910s, and the creation of an Industrial Pole in the 1970s. When rubber went bust, regional elites sought to transform Manaus from an extractive enclave into an industrial center. The result was the Manaus Free Trade Zone, inaugurated in 1967, which would also include an industrial district, the Industrial Pole of Manaus, launched in 1972. The Free Trade Zone created extraordinary economic and demographic growth but, paradoxically, it also reproduced some of the dynamics of the rubber era. It was based on exploitative labor regimes and remained dependent on import-export houses and consumption within the city. Moreover, it ultimately exacerbated the city’s extractive demands on the rainforest and its peoples.